Partially dissecting the steady-state electron fluxes in Photosystem I in wild-type and pgr5 and ndh mutants of Arabidopsis - Kou, Jiancun; Takahashi, Shunichi; Fan, Da-Yong; Badger, Murray R.; Chow, Wah S. (Frontiers in Plant Science, 2015)
Cyclic electron flux (CEF) around Photosystem I (PS I) is difficult to quantify. We obtained the linear electron flux (LEFO2) through both photosystems and the total electron flux through PS I (ETR1) in Arabidopsis in CO2-enriched air. DeltaFlux = ETR1 – LEFO2 is an upper estimate of CEF, which consists of two components, an antimycin A-sensitive, PGR5 (proton gradient regulation 5 protein)-dependent component and an insensitive component facilitated by a chloroplastic nicotinamide adenine dinucleotide dehydrogenase-like complex (NDH). Using wild type as well as pgr5 and ndh mutants, we observed that (1) 40% of the absorbed light was partitioned to PS I; (2) at high irradiance a substantial antimycin A-sensitive CEF occurred in the wild type and the ndh mutant; (3) at low irradiance a sizable antimycin A-sensitive CEF occurred in the wild type but not in the ndh mutant, suggesting an enhancing effect of NDH in low light; and (4) in the pgr5 mutant, and the wild type and ndh mutant treated with antimycin A, a residual DeltaFlux existed at high irradiance, attributable to charge recombination and/or pseudo-cyclic electron flow. Therefore, in low-light-acclimated plants exposed to high light, DeltaFlux has contributions from various paths of electron flow through PS I.